BENTUK DAN DAMPAK KEKERASAN DI TEMPAT KERJA (WORKPLACE BULLYING) PADA BURUH PABRIK DI GRESIK - Hidayati, Nurul; Rahayuningsih, Idha (PSIKOSAINS (Jurnal Penelitian dan Pemikiran Psikologi), 2014)
The form of violence change based on age. Workplace bullying is a serious problems that happen until nowdays. It includes physical bullying, verbal bullying, psychological bullying, and social bullying. Bullying is an aggressive behavior that happened on purpose to make physical discomfort or psychological discomfort to others. Meanwhile, Gresik is an industrial city where many workers from Gresik and other city in Indonesia make a living in this city. The position of workers that usually inferior has made factory workers become a potential objects of workplace bullying. This research is a qualitative research and it aims is to know the forms and the effects of workplace bulyying happened at factory workers in Gresik. This research subjects are twenty factory workers. This research using interview to collect data. In long term, researcher hope that the result of this research can be used by the government in Gresik to make rules to protect the factory workers in Gresik area from workplace bullying.